Efficacy and Safety of IncobotulinumtoxinA in the Treatment of Lower Limb Spasticity in Japanese Subjects - Masakado, Yoshihisa; Kagaya, Hitoshi; Kondo, Kunitsugu; Otaka, Yohei; Dekundy, Andrzej; Hanschmann, Angelika; Geister, Thorin L.; Kaji, Ryuji (Frontiers in Neurology, 2022)
Objective To confirm the efficacy and safety of incobotulinumtoxinA (Xeomin®, Merz Pharmaceuticals GmbH; total dose 400 U) in Japanese subjects with lower limb (LL) post-stroke spasticity, using the Modified Ashworth Scale spasticity score for the plantar flexors (MAS-PF). Methods This Phase III study (Japic clinical study database No. CTI-153030, 7 October 2015) included a double-blind, 12-week main period (MP), in which 208 subjects were randomized to receive one injection cycle of incobotulinumtoxinA 400 U (n = 104) or placebo (n = 104) into the pes equinus muscles, and an open-label extension (OLEX) that enrolled 202 subjects who received three injection cycles, 10–14 weeks in duration (the last cycle was fixed at 12 weeks). Changes in MAS-PF for incobotulinumtoxinA versus placebo from baseline to Week 4 of the MP and to the end of cycle visits in the OLEX were evaluated. Results The area under the curve of the change in MAS-PF was statistically significantly greater with incobotulinumtoxinA versus placebo in the MP (mean: –7.74 vs. –4.76; least squares mean: –8.40 vs. –5.81 [p = 0.0041]). In the OLEX, mean changes in MAS-PF from baseline to end of study showed continued improvement with repeated injections. No new safety concerns were observed with incobotulinumtoxinA treatment. Its efficacy and safety were consistent regardless of length of injection cycle interval in the OLEX. Conclusion This study demonstrated that incobotulinumtoxinA (total dose 400 U) injected at flexible intervals (10–14 weeks) is an effective and well-tolerated treatment for LL spasticity in Japanese subjects using flexible injection intervals of 10–14 weeks.